Colistin-induced pulmonary toxicity involves the activation of NOX4/TGF-β/mtROS pathway and the inhibition of Akt/mTOR pathway. (May 2022) - Dai, Chongshan; Li, Meng; Sun, Tun; Zhang, Yuan; Wang, Yang; Shen, Zhangqi; Velkov, Tony; Tang, Shusheng; Shen, Jianzhong
Abstract: Colistin therapy can cause pulmonary toxicity, however, our understanding of the underlying molecular mechanism remains incomplete. This study aimed to investigate the molecular mechanism of colistin-induced pulmonary toxicity in vitro and in vivo . Our results showed that intraperitoneal colistin treatment significantly increased the expression of TGF-β and NOX4 protein and mRNA, then triggers oxidative stress, mitochondrial dysfunction, and apoptosis in the lung tissue of mice and A549 cells. Moreover, colistin treatment significantly increased levels of mitochondrial ROS (mtROS) and autophagy flux in A549 cells. Inhibition of NOX4 protected A549 cells against colistin-induced mtROS and apoptosis. Colistin treatment also down-regulated the expression of p-Akt and p-mTOR proteins (all P  < 0.05 or 0.01) in lung tissues of mice or A549 cells. Inhibition of autophagy or Akt pathways by chloroquine (CQ), 3-Methyladenine (3-MA) or LY294002 promoted colistin-induced mitochondrial damage, and caspase-dependent cellular apoptosis. Whereas, activation of autophagy by rapamycin pretreatment of A549 cells partly abolished colistin-induced cytotoxicity, mitochondrial dysfunction, and apoptosis. This is first study to show that colistin-induced pulmonary toxicity involves the activation of TGF-β/NOX4/mtROS pathway and the inhibition of Akt/mTOR pathway in lung tissues of mice and highlights the key protective role of autophagy activation. Graphical abstract: Image 1 Highlights: Colistin treatment can cause marked mitochondrial dysfunction and cellular apoptosis in vitro and in vivo . Activation of NOX4/TGF-β/mitochondrial ROS pathway plays a critical role in colistin-induced oxidative stress damage. Colistin treatment activates autophagy and autophagy flux via the inhibition of Akt/mTOR pathway. Rapamycin can protect against colistin-induced pulmonary toxicity via the activation of autophagy.